1981
DOI: 10.1111/j.1432-1033.1981.tb05172.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Adenosine Triphosphatase Activity of the ATP-Dependent Deoxyribonuclease, of Bacillus subtilis

Abstract: Studies on the specificity of the ATP-dependent DNase of Bacillus subtilis 168, carried out with pure enzyme at the optimal conditions for its action, have shown that the substrate is double-stranded linear DNA. Linear singlestranded DNA (separated strands of B. subtilis DNA and linear phage fd DNA) is not attacked, neither are there any circular forms (supercoiled or nicked simian virus 40 and circular single-stranded fd DNAs). The doublestranded DNA can be completely hydrolysed, the limit products being, alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
3

Year Published

1981
1981
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…The addAS and addB72 mutant strains have impairments in different subunits of the AddBCD enzyme (3,11,12,19). When the addAS mutation was introduced into the addB72 genetic background, we observed that the double mutant strains were as deficient as the addAS parent strain ( Table 2).…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…The addAS and addB72 mutant strains have impairments in different subunits of the AddBCD enzyme (3,11,12,19). When the addAS mutation was introduced into the addB72 genetic background, we observed that the double mutant strains were as deficient as the addAS parent strain ( Table 2).…”
Section: Methodsmentioning
confidence: 80%
“…The most economical assumption is that the addA and addB mutations define an epistatic group. In the absence of the AddABC enzyme (addA5 or addA5 addB72 mutant strains), there was still a high residual level of recombination in B. subtilis (3,11,13) (Table 2). We have ruled out the possibility that the mutant enzymes retained their recombination activity, because many addA5 double mutant strains (Table 2) were deficient in recombination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A processive double-strand exonuclease, a single-strand exonuclease, a DNA-dependent ATPase, and an ATP-dependent double-strand unwinding function were associated with the purified B. subtilis ExoV analog (12,32,38) as they were with E. coli ExoV (15).…”
mentioning
confidence: 99%